2022
DOI: 10.17241/smr.2022.01501
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Stress and Anxiety to Viral Epidemics-9 (SAVE-9) Scale and Relationship With Insomnia or Depression Among Healthcare Workers Who Witnessed Patient’s Death in COVID-19 Pandemic

Abstract: Background and Objective We tested the psychometric properties of the Stress and Anxiety to Viral Epidemics-9 (SAVE-9) scale among healthcare workers who experienced patients’ deaths.Methods From June 2nd to 10th, 2022, an anonymous, online survey was administered to medical doctors and nursing professionals who witnessed the deaths of patients they cared for during the last two years. Participants demographic characteristics and responses to the SAVE-9, Generalized Anxiety Disorder-7 (GAD-7), Patient Health Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Though the three items (items 6, 7, and 9) of the SAVE-9 can be applied to measure healthcare workers' work-related stress in response to the viral epidemic, 25 it was not more informative than the SAVE-6 and SAVE-9. 24 Thus, these results showed that we could select a specific rating scale (SAVE-6 or each worker's version of SAVE-9) depending on the purposes of the study. This study has some limitations.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Though the three items (items 6, 7, and 9) of the SAVE-9 can be applied to measure healthcare workers' work-related stress in response to the viral epidemic, 25 it was not more informative than the SAVE-6 and SAVE-9. 24 Thus, these results showed that we could select a specific rating scale (SAVE-6 or each worker's version of SAVE-9) depending on the purposes of the study. This study has some limitations.…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, the single-factor model of the SAVE-9 scale cannot be more informative than the SAVE-6 among this firefighters sample (Figure 2), similar to the previous study on healthcare workers. 24 According to these results, applying the SAVE-9 scale provides no more benefits than using the SAVE-6 scale. Moreover, we can apply the SAVE-6 when we need to assess the viral anxiety of workers briefly.…”
Section: Discussionmentioning
confidence: 92%
“…This is a continuation of the previous study. 18 We distributed the survey link via the hospital’s intranet to recruit doctors and nursing professionals who witnessed the deaths of patients they cared for during the last two years. They voluntarily participated in this anonymous online survey, and we rewarded their participation with a five-dollar gift coupon.…”
Section: Methodsmentioning
confidence: 99%
“…This study used data obtained from a previous study conducted through anonymous online surveying of healthcare workers at a tertiary hospital from June 2 to 10, 2022 (D. Lee et al., 2022). We recruited healthcare workers (doctors and nurses) who experienced the deaths of patients over the preceding 2‐year period.…”
Section: Methodsmentioning
confidence: 99%